Characteristics of Mothers' Depressive Illness as Predictors for Emotional and Behavioural Problems in Children in a Sri Lankan Setting - Rohanachandra, Y.M.; Prathapan, S.; Wijetunge, G.S. (Asian Journal of Psychiatry, 2018)
Attached
Keywords: Maternal depression; Psychological problems in children